2006
DOI: 10.1111/j.1469-0691.2005.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of fusobacterium infections in humans: recent experience with fusobacterium bacteraemia

Abstract: A retrospective study was conducted of 26 adult cases of fusobacterium bacteraemia that occurred between 1998 and 2003 at Center Hospitalier Universitaire de Grenoble, France. Most patients presented with pre-existing adverse medical conditions, including evolving malignant diseases (eight patients), recent surgery (four patients), and chronic organ failure (six patients). Only one patient presented with a classic Lemierre's syndrome. These results suggest an opportunistic pattern of modern fusobacterium infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
4
15
0
Order By: Relevance
“…However, in the current review, a total of 21 patients were found to have F. necrophorum bacteremia following a throat infection but with no intracranial or metastatic infection. Three of these patients had deep neck infection; one had a peritonsillar abscess (313), and two had parapharyngeal abscesses (130,227). Six cases had proven internal jugular vein thrombophlebitis.…”
Section: Natural History and Forms Of F Necrophorum Septicemiamentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the current review, a total of 21 patients were found to have F. necrophorum bacteremia following a throat infection but with no intracranial or metastatic infection. Three of these patients had deep neck infection; one had a peritonsillar abscess (313), and two had parapharyngeal abscesses (130,227). Six cases had proven internal jugular vein thrombophlebitis.…”
Section: Natural History and Forms Of F Necrophorum Septicemiamentioning
confidence: 99%
“…Epaulard et al (130) reported that among 6,274 bacteremias over a 5-year period at one institution, 26 (0.4%) were adult cases of Fusobacterium sp. bacteremia.…”
Section: Anaerobic Bacteremiamentioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of suspicion is needed and usually the syndrome is not diagnosed until microbiology results are available 1017. With suspected clinical picture imaging modalities usually confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The organism is usually isolated from blood cultures. Other microbiological specimens include synovial fluid, skin pustules and pus from liver abscesses, empyema and a bronchoscopic aspirate 1017…”
Section: Discussionmentioning
confidence: 99%